1984
DOI: 10.1017/s000335610002763x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rates of outflow of protein supplement from the rumen by determining the rate of excretion of chromium-treated protein supplements in faeces

Abstract: An experiment was conducted to study the possibility of using marker concentration in faeces to estimate rumen outflow of Cr-treated protein supplements and the liquid phase (PEG). There were no significant differences in the outflow of each marker from the rumen when determined directly from rumen or indirectly from faeces, suggesting that faeces could be used to measure the outflow from the rumen without the need for surgical preparation of the animals. The outflow rate of the liquid phase was considerably f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The small effect of Cr treatment on the particle size distribution of protein supplements was similar to our early observations with fish meal (Elimam and 0rskov, 1981) and, together with the nonsignificant effects on the density, suggested that Cr-treated protein supplements were likely to behave in a manner similar to the 2. The relationship between the intake of a mixed diet of 500 g roughages and 500 g concentrates per kg. and fractional outflow rates per h of fish meal from the rumen of high-yielding dairy cows in mid lactation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The small effect of Cr treatment on the particle size distribution of protein supplements was similar to our early observations with fish meal (Elimam and 0rskov, 1981) and, together with the nonsignificant effects on the density, suggested that Cr-treated protein supplements were likely to behave in a manner similar to the 2. The relationship between the intake of a mixed diet of 500 g roughages and 500 g concentrates per kg. and fractional outflow rates per h of fish meal from the rumen of high-yielding dairy cows in mid lactation.…”
Section: Discussionsupporting
confidence: 83%
“…In previous trials (Elimam and 0rskov, 1981) with Cr-treated fish meal (FM), it was found that 7-2 g sodium dichromate per 100 g dry matter (DM) was adequate to render FM completely undegradable without affecting particle size distribution. In previous trials (Elimam and 0rskov, 1981) with Cr-treated fish meal (FM), it was found that 7-2 g sodium dichromate per 100 g dry matter (DM) was adequate to render FM completely undegradable without affecting particle size distribution.…”
Section: Chromium Preparationsmentioning
confidence: 99%
“…The liquid outflow rate was about twice that of particles of fish meal which agrees well with a similar comparison in sheep (Elimam and 0rskov, 1984). The liquid outflow rate was about twice that of particles of fish meal which agrees well with a similar comparison in sheep (Elimam and 0rskov, 1984).…”
Section: Comparison Oj Outflow Rates Oj Different Digesta Fractionssupporting
confidence: 88%
“…Values after the peak in the linear descending portion of the curve were used for the regression analysis as described by Elimam and 0rskov (1984) and based on the work of Grovum and Williams (1977). Values after the peak in the linear descending portion of the curve were used for the regression analysis as described by Elimam and 0rskov (1984) and based on the work of Grovum and Williams (1977).…”
Section: Calculation Of Rumen Outflow Rate and Rumen Retention Timementioning
confidence: 99%
“…Since the declining rate of faecal Cr concentration has been shown to be highly correlated with rumen dilution rate of Cr-mordanted supplements (Elimam and 0rskov, 1984b;Guada Vallepuga, Castrillo Gonzalez, Vega Garcia and Gasa Gaso, 1986), it is assumed to be an acceptable estimate of the fractional outflow rate of protein supplements from the rumen.…”
Section: Rumen Outflow Rates Of Cr-mordanted Supplementsmentioning
confidence: 99%